Meritocracy, ability orientation and 'discrimination' - Kariya, Takehiko; Burtscher, Michael (Education Reform and Social Class in Japan, 2013)
I thought that once the high school entrance exams were over, everything would be play and fun, and that freed from studying, I could finally relax. But while I am glad I got into the school I wanted, I do not feel any better. One of the things that struck me was that once one gets into high school, part of the subjects are taught in classes according to proficiency level ...